Adenoidal nasopharyngeal ratio and its correlation with skeletal class II malocclusion in children: A cross-sectional study - A.R, Dr. Yusuf; Fernandes, Dr. Sharrianne; Roy, Dr. Priya; Ganiger, Dr. Chanamallappa; Pawar, Dr. Renuka; Phaphe, Dr. Sandesh; Mane, Dr. Pratap (South Eastern European Journal of Public Health, 2024)
Introduction: The relationship between skeletal class II malocclusion and airway has gained significant interest in the field of orthodontics and is crucial for accurate diagnosis and treatment planning. Various etiologies contribute to airway obstruction, which may disrupt the breathing pattern and swallowing functions, affecting the development of the craniofacial complex and consequently resulting in the development of skeletal Class II malocclusion. Adenoid hypertrophy (AH) has been linked to cardiopulmonary complications, craniofacial growth disturbances and obstructive sleep apnea. Patients with AH often exhibit a characteristic adenoid face and mouth breathing pattern with a narrow constricted maxillary arch and retrognathic mandible. Adenoidal- nasopharyngeal ratio is a simple linear measurement obtained from lateral cephalograms that can reliably express adenoidal size and patency of the nasopharyngeal airway and give further insight into the etiology of development of class II malocclusion and correlation with the same. Materials and methods: Sample of 40 individuals between 10-16 years of age was divided into two groups of 20 each based on their ANB angle, Group A comprised of individuals showing skeletal class I and group B showing skeletal class II malocclusion respectively. Lateral cephalograms were taken and AN ratio was assessed using the Fujioka et al method for both groups. AN ratios were correlated with skeletal class of malocclusion and values of both groups were compared.